Modified cellulose, nanocellulose, and methods of making and click chemistry applications thereof

CN117209615BActive Publication Date: 2026-10-30INT CENT FOR BAMBOO & RATTAN
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311202968.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2026-10-30
Estimated Expiration
2043-09-18

AI Technical Summary

Technical Problem

[0007]本发明的目的在于提供一种改性纤维素、纳米纤维素及其制备方法与点击化应用,用于解决现有技术中制备过程繁琐、耗时等问题,简单高效地实现纤维素改性以及纤维素的纳米纤丝化,简化了具有点击化学活性位点的纳米纤维素的步骤,极大地缩短了制备的时间

Benefits of technology

[0047]本发明提出一种改性纤维素、纳米纤维素制备的新方法,通过向纳米纤维素表面引入点击反应所需的烯基,为纳米纤维素的点击功能化构建了一种全新的通用并高效的反应平台。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117209615B_ABST
    Figure CN117209615B_ABST
Patent Text Reader

Abstract

The present application relates to natural high polymer material technical field, especially a kind of modified cellulose, nanocellulose and its preparation method and click chemical application.It is prepared that the method of the modified cellulose includes: S1: cellulose is pre-activated in the mixed solvent containing dimethyl sulfoxide, strong base and water, and pre-activated cellulose slurry is obtained;S2: the pre-activated cellulose slurry is mixed with esterification agent to carry out esterification reaction, and the modified cellulose is obtained;The present application proposes a kind of new method for preparing modified cellulose, nanocellulose, by introducing the alkenyl group required for click reaction to the surface of nanocellulose, a kind of new general and efficient reaction platform is constructed for the click functionalization of nanocellulose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of natural polymer materials technology, and in particular to a modified cellulose, nanocellulose, and their preparation methods and applications. Background Technology

[0002] Cellulose is the most abundant natural polymer on Earth and the most widely distributed and abundant polysaccharide material in nature. Nanocellulose is a natural nanomaterial with characteristics such as renewability, good biocompatibility, biodegradability, and excellent mechanical properties. However, the surface of nanocellulose is rich in hydroxyl groups, exhibiting strong hydrophilicity and a limited surface chemical composition, resulting in limited product properties and restricting its application range and fields. Specifically, most polymer materials are currently hydrophobic, and the high hydrophilicity of nanocellulose leads to poor interfacial compatibility with hydrophobic elastomers and a tendency to aggregate in polymer matrices. Therefore, the compatibility between nanocellulose and the polymer matrix is ​​crucial for achieving its performance enhancement in composite materials. Furthermore, unmodified nanocellulose struggles to form covalent bonds with hydrophobic polymers, thus reducing its reinforcing effect and failing to leverage its superior mechanical properties. Therefore, modification of nanocellulose is an important prerequisite for its application in polymer composites.

[0003] However, the chemical modification process of nanocellulose is complex and cumbersome, requiring a large amount of energy and organic solvents, and is time-consuming. In addition, these modification methods are relatively weak in versatility, making it difficult to achieve a "one-to-many" universal modification technology, that is, each modification reaction can only target one compound, rather than the same modification method can prepare different functionalized nanocelluloses.

[0004] In recent years, the construction and functionalization of natural polymer materials based on click chemistry strategies have gained significant attention due to the high selectivity, modularity, rapid reaction speed, and high yield of click chemistry. Furthermore, click chemistry offers advantages such as simple conditions, the ability to use no or benign solvents, and insensitivity to water and oxygen. Click chemistry can be used to construct different molecular structures on the surface of nanocellulose, thereby controlling its surface properties (such as hydrophilicity and hydrophobicity), or to covalently link nanocellulose with other materials to prepare high-performance functional composite materials, thus increasing the added value of nanocellulose and expanding its application areas. Introducing clickable side chains or chain ends on the surface of nanocellulose is a necessary condition before using click chemistry for modification or functionalization. However, current research on click chemistry for cellulose modification mainly focuses on the "post-functionalization" part, with relatively little research on the efficient preparation and reaction mechanisms of bamboo-based nanocellulose modified with clickable groups. Currently, the general process for preparing click-reaction functionalized cellulose nanofibers involves first preparing cellulose nanocrystals (CNC) using the traditional concentrated sulfuric acid method, or preparing cellulose nanofibers (CNF) using mechanical or chemical methods. Then, various chemical modification methods, such as esterification and etherification, are used to modify the surface of the cellulose nanofibers, introducing clickable groups such as thiol (-SH), alkynyl (-CC), alkenyl (-C=C-), azide (-N3), and amino (-NH2) groups. Subsequently, the cellulose nanofibers are polymerized with other clickable monomers or linked with other clickable polymers through a click reaction, ultimately obtaining cellulose nanofibers or cellulose nanofiber functionalized polymer composites with different surface chemical properties. The main drawback is that before introducing the clickable groups, cellulose nanofibers usually need to be prepared first, followed by dehydration or solvent replacement. The drying process can cause irreversible aggregation of the cellulose nanofibers, reducing their surface reactivity and leading to "keratinization." The solvent replacement process is cumbersome and consumes a large amount of organic solvent, resulting in a complex and time-consuming chemical modification process for cellulose nanofibers.

[0005] Therefore, developing a simple and efficient method for the chemical modification and functionalization of nanocellulose would greatly advance its application in the field of functional polymer composites.

[0006] In view of this, the present invention is proposed. Summary of the Invention

[0007] The purpose of this invention is to provide a modified cellulose, nanocellulose, and their preparation method and clickable application, which solves the problems of cumbersome and time-consuming preparation processes in the prior art, and realizes cellulose modification and nanofibrillation of cellulose in a simple and efficient manner. It simplifies the steps of nanocellulose with clickable chemical active sites and greatly shortens the preparation time.

[0008] The specific technical solution of the present invention is as follows:

[0009] In a first aspect, the present invention provides a method for preparing modified cellulose, comprising:

[0010] S1: The cellulose pulp is pre-activated using a mixed solvent containing dimethyl sulfoxide, a strong base and water to obtain a pre-activated cellulose pulp;

[0011] S2: The pre-activated cellulose slurry is mixed with an esterifying agent and subjected to an esterification reaction to obtain modified cellulose;

[0012] The esterifying agent is an acid anhydride compound containing alkenyl and carboxyl groups.

[0013] This invention discovers that by pre-activating cellulose with a mixed solvent of dimethyl sulfoxide / strong alkali / water, and simultaneously using an anhydride molecule compound with active alkenyl and carboxyl groups as an esterifying agent to carry out the esterification reaction of cellulose, carboxylic acid groups (-COOH) and the active alkenyl groups (-C=C-) required for the reaction can be introduced onto the surface of cellulose at the same time, and the reaction is fast and the yield is high.

[0014] Preferably, the anhydride compound containing alkenyl and carboxyl groups includes norbornene anhydride or oxamanide.

[0015] Preferably, in step S1, 10 to 30 parts of cellulose are added to a mixed solvent containing 260 to 550 parts of dimethyl sulfoxide, 4 to 8 parts of a strong alkali and 20 to 100 parts of water, and pre-activated under microwave.

[0016] The present invention has found that pre-activation of the above-mentioned mixed solvent under microwave conditions can significantly enhance the activation degree of cellulose by the activation system, thereby improving the reaction efficiency of the subsequent esterification reaction, resulting in an increase in the carboxyl content after esterification; and can make the subsequent esterification reaction conditions more mild.

[0017] More preferably, the pre-activation time under microwave is 10 to 60 seconds.

[0018] More preferably, the strong alkali includes one or more of potassium methoxide, potassium tert-butoxide, sodium hydroxide, and potassium hydroxide.

[0019] Preferably, in step S2, 40-168 parts of the esterifying agent are mixed with 10-30 parts of the pre-activated cellulose slurry, and the esterification reaction is carried out at 20-100°C for 10-60 minutes; after the reaction, the mixture is washed with water and filtered until neutral to obtain modified cellulose, i.e., olefinized cellulose.

[0020] More preferably, the esterification reaction is carried out at room temperature for 5 to 120 minutes; even more preferably, the reaction time is 10 minutes.

[0021] Preferably, the cellulose is bamboo-based cellulose, and the preparation method of the bamboo-based cellulose includes:

[0022] 1) Soak 40-400 parts of 30-60 mesh bamboo powder in water and dry it at 80℃-90℃ to obtain thin-walled cells and bamboo fibers;

[0023] 2) The thin-walled cells and bamboo fibers were soaked in 6-10% peracetic acid solution and 4-6% potassium hydroxide solution respectively, then heated at 80-95℃ for 4-6 hours, and finally washed with water to obtain bamboo-based cellulose from the thin-walled cells and bamboo fibers respectively.

[0024] Secondly, the present invention also provides a modified cellulose, which is prepared by the above-described preparation method.

[0025] Thirdly, the present invention further provides a method for preparing nanocellulose, comprising: mixing the modified cellulose with water to obtain a modified cellulose suspension; adjusting the pH of the suspension to alkaline, and then subjecting it to ultrasonic treatment or high-pressure homogenization.

[0026] Compared to traditional methods that first prepare nanocellulose and then modify it with alkenylation to construct a nanocellulose click functionalization platform, this invention produces reactive olefin functional groups suitable for click chemistry reactions on the surface of nanocellulose during the preparation of nanocellulose, providing active reaction sites for click chemical functionalization modification. This invention provides a simple and efficient one-pot method for constructing a nanocellulose click functionalization reaction platform, allowing the reactive alkenyl groups on the nanocellulose surface to directly react with other clickable monomers or polymers through click chemistry to generate nanocellulose materials or composite materials with different surface properties or functions.

[0027] This invention deprotonates the carboxyl groups on the surface of modified cellulose to form charged groups, generating electrostatic repulsion between filaments, which can accelerate the nanofiber disintegration of filaments.

[0028] Preferably, the pH of the suspension is adjusted to 8-10.

[0029] Preferably, the amount of modified cellulose in the modified cellulose suspension is 0.5 to 1.0 wt%.

[0030] Preferably, the ultrasonic treatment time is 5 to 15 minutes; the high-pressure homogenization treatment is performed 3 to 5 times; more preferably 4 times.

[0031] In a preferred embodiment of the present invention, the method for preparing the nanocellulose includes:

[0032] 1) Add 10-30 parts dry weight of cellulose to a mixed solvent containing 260-550 parts dimethyl sulfoxide (DMSO), 4-8 parts strong alkali, and 60-100 parts water (H2O), and pre-activate it under microwave for 10-60 seconds to obtain pre-activated cellulose slurry.

[0033] 2) Dissolve 40-168 parts of the esterifying agent in 110-400 parts of DMSO, then add it to the pre-activated cellulose slurry, and esterify at 20-100°C for 5-120 min; preferably at room temperature for 10 min. After the reaction, wash with water and filter until neutral to obtain modified cellulose, i.e. olefinized cellulose.

[0034] 3) Mix olefinized cellulose with water to obtain a suspension with a mass fraction of 0.5-1.0%, adjust the pH value to 8-10, and then perform ultrasonic treatment for 5-15 minutes or high-pressure homogenization treatment 3-5 times; preferably, high-pressure homogenization treatment 4 times to obtain olefinized nanocellulose.

[0035] Fourthly, the present invention provides a nanocellulose, which is prepared by the above-described preparation method.

[0036] Fifthly, the present invention provides the application of the modified cellulose or the nanocellulose in click reactions.

[0037] Preferably, the method for preparing the hydrophobic cellulose includes: mixing ethanol, a thiol compound and the modified cellulose, and carrying out a thiol-olefin click chemistry reaction under ultraviolet irradiation.

[0038] Preferably, the method for preparing the hydrophobic nanocellulose includes:

[0039] 1) Mix the nanocellulose with water, then adjust the pH to acidic, and wash, filter, and dehydrate repeatedly; preferably, adjust the pH to 2-3;

[0040] 2) Solvent replacement with ethanol was used to obtain a nanocellulose ethanol suspension;

[0041] 3) The thiol compound and the nanocellulose ethanol suspension were mixed and subjected to a thiol-olefin click chemistry reaction under ultraviolet irradiation.

[0042] Preferably, in the thiol-olefin click chemistry reaction, the wavelength of the ultraviolet light is 320-400 nm; more preferably, the wavelength of the ultraviolet light is 365 nm.

[0043] Preferably, the thiol compound includes one or more of dodecyl thiol, tridecyl thiol, tetradecyl thiol, pentadecyl thiol, hexadecyl thiol, and octadecyl thiol.

[0044] Fifthly, the present invention provides a hydrophobic nanocellulose, which is prepared by the above-described preparation method.

[0045] In a sixth aspect, the present invention provides a hydrophobic cellulose, which is prepared by the above-described preparation method.

[0046] Based on the above technical solution, the beneficial effects of the present invention are as follows:

[0047] This invention proposes a novel method for preparing modified cellulose and nanocellulose. By introducing alkenyl groups required for click reactions onto the surface of nanocellulose, a new, universal, and efficient reaction platform is constructed for the click functionalization of nanocellulose. Attached Figure Description

[0048] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0049] Figure 1 This is a schematic diagram of the reaction of norbornene-modified cellulose prepared in Example 1 of the present invention to generate groups with negative charges on the surface;

[0050] Figure 2 These are physical images of norborneol-modified cellulose and norborneol-modified nanocellulose prepared using microcrystalline cellulose as raw material in Example 1 of this invention; wherein, (a) is a physical image of norborneol-modified cellulose, and (b) is a physical image of norborneol-modified nanocellulose.

[0051] Figure 3 Characterization diagram of norborneol-modified cellulose prepared from microcrystalline cellulose in Example 1 of the present invention; wherein, (a) is the Fourier transform infrared spectrum of norborneol-modified cellulose, and (b) is the atomic force microscopy (AFM) morphology diagram of norborneol-modified nanocellulose.

[0052] Figure 4 Nuclear magnetic resonance spectra of norbornene-modified cellulose and hydrophobic cellulose prepared from microcrystalline cellulose in Example 1 of this invention;

[0053] Figure 5 The images show actual pictures of the hydrophobic cellulose and hydrophobic nanocellulose prepared in Example 1 of this invention; wherein, (a) is an actual picture of hydrophobic cellulose and (b) is an actual picture of hydrophobic nanocellulose.

[0054] Figure 6 Images showing the water contact angles of hydrophobic cellulose and hydrophobic nanocellulose prepared in Example 1 of this invention; wherein, (a) is the water contact angle image of hydrophobic cellulose, and (b) is the water contact angle image of hydrophobic nanocellulose;

[0055] Figure 7 Characterization diagrams of oxamanic anhydride-modified cellulose prepared from microcrystalline cellulose in Example 2 of the present invention; wherein, (a) is the Fourier transform infrared spectrum of oxamanic anhydride-modified cellulose, and (b) is the atomic force microscopy (AFM) morphology diagram of oxamanic anhydride-modified nanocellulose.

[0056] Figure 8 Images showing the water contact angles of hydrophobic cellulose and hydrophobic nanocellulose prepared in Example 2 of this invention; wherein, (a) is the water contact angle image of hydrophobic cellulose, and (b) is the water contact angle image of hydrophobic nanocellulose;

[0057] Figure 9 The images shown are of olefinized bamboo-based cellulose and bamboo-based nanocellulose colloids prepared from bamboo-based cellulose as raw material in Example 3 of this invention; wherein, (a) is an image of olefinized bamboo-based cellulose and (b) is an image of bamboo-based nanocellulose colloids.

[0058] Figure 10 Characterization diagrams of olefinized bamboo-based cellulose prepared from bamboo-based cellulose in Example 3 of the present invention; wherein, (a) is the Fourier transform infrared spectrum of olefinized bamboo-based cellulose, and (b) is the atomic force microscopy (AFM) morphology diagram of olefinized bamboo-based nanocellulose.

[0059] Figure 11 Images showing the water contact angles of hydrophobic cellulose and hydrophobic nanocellulose prepared in Example 3 of this invention; wherein, (a) is the water contact angle image of hydrophobic cellulose, and (b) is the water contact angle image of hydrophobic nanocellulose. Detailed Implementation

[0060] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0061] Unless otherwise specified, all raw materials used in the examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art. All parts in the following examples are by weight.

[0062] Example 1

[0063] This embodiment first provides a modified cellulose—norborneol-modified microcrystalline cellulose, the preparation method of which includes the following steps:

[0064] 1) Prepare a dimethyl sulfoxide (DMSO) / potassium hydroxide (KOH) / water (H2O) solvent: Dissolve 4 parts KOH in 60 parts water, then add 440 parts DMSO to dissolve, and shake to mix.

[0065] 2) Weigh 20.0 parts of dry microcrystalline cellulose and add it to the DMSO / KOH / H2O quasi-solvent prepared in step 1). Pre-activate it under microwave for 10 seconds to obtain pre-activated cellulose slurry.

[0066] 3) Weigh 81 parts of norbornene adienoic anhydride, dissolve the weighed norbornene adienoic anhydride in 110 parts of DMSO, and then add it to the pre-activated cellulose slurry from step 2). React at room temperature for 10 minutes, then wash with water and filter until neutral to obtain norbornene adienoic anhydride-modified cellulose. See the reaction diagram below. Figure 1 .

[0067] This embodiment further provides a nanocellulose—norbornene group-modified nanocellulose, the preparation method of which includes the following steps:

[0068] The norbornene-modified cellulose was redispersed in water to prepare a cellulose suspension with a mass fraction of 0.5-0.6%, the pH was adjusted to 9.0, and then ultrasonic treatment was performed for 10 minutes to obtain norbornene-modified nanocellulose with a yield of about 90%, a diameter of 3-6 nm, a length of 200-500 nm, and an aspect ratio of 89±37.

[0069] The carboxyl content in the norbornene group-modified nanocellulose was determined by conductivity titration, and the result showed that the value was 0.70 mmol / g.

[0070] Among them, physical images of norbornene-modified cellulose and norbornene-modified nanocellulose are shown below. Figure 2 Characterization diagram of norbornene-modified cellulose is shown in [reference needed]. Figure 3 .

[0071] This embodiment also provides a hydrophobic cellulose, the preparation method of which includes the following steps:

[0072] Disperse the 2 parts of norbornene modified cellulose obtained in step 3) above in 100 parts of ethanol, then add 6 parts of hexadecyl mercaptan, stir for 10 minutes to obtain a mixture;

[0073] The mixture was placed under a 365nm wavelength UV lamp and irradiated for 24 hours. It was then repeatedly washed, filtered, and dried with ethanol and water to obtain hydrophobic cellulose.

[0074] The contact angle of the hydrophobic cellulose was tested to be 101°.

[0075] This embodiment also provides a hydrophobic nanocellulose, the preparation method of which includes the following steps:

[0076] 1) The norbornene-modified anhydride nanocellulose obtained above was mixed with water, the pH was adjusted to 2-3 for protonation, and then filtered and dehydrated in a Buchner funnel. Ethanol was added repeatedly for solvent replacement and filtration. Then the norbornene-modified nanocellulose was dispersed in ethanol to obtain a norbornene-modified nanocellulose ethanol suspension.

[0077] 2) Add 6 parts of hexadecyl mercaptan to the above norbornene group modified nanocellulose ethanol suspension (2 parts), stir for 10 minutes, then place the mixture under a 365nm wavelength UV lamp for 24 hours, and repeatedly wash, filter and dry with ethanol and water to obtain hydrophobic nanocellulose.

[0078] The contact angle of the hydrophobic nanocellulose was tested to be 110°. The nuclear magnetic resonance spectra of norbornene-modified cellulose and hydrophobic cellulose prepared from microcrystalline cellulose in Example 1 are shown below. Figure 4 The physical images of the hydrophobic cellulose and hydrophobic nanocellulose prepared in Example 1 are shown below. Figure 5 See water contact angle image. Figure 6 .

[0079] Example 2

[0080] This embodiment first provides a modified cellulose—oxoanhydride-modified microcrystalline cellulose, the preparation method of which includes the following steps:

[0081] 1) Prepare a dimethyl sulfoxide (DMSO) / potassium hydroxide (KOH) / water (H2O) standard solvent. Dissolve 4 parts of KOH in 60 parts of water, then add 440 parts of DMSO to dissolve, and shake to mix well.

[0082] 2) Weigh 20.0 parts of dry microcrystalline cellulose and add it to DMSO / KOH / H2O quasi-solvent. Pre-activate it in microwave for 10 seconds.

[0083] 3) Weigh 167 parts of oxaic anhydride, dissolve the weighed oxaic anhydride in 400 parts of DMSO, and then add it to the pre-activated microcrystalline fiber mixture from step 2). React at room temperature for 30 minutes, then wash with water and filter until neutral to obtain oxaic anhydride-modified cellulose. The characterization diagram of the prepared oxaic anhydride-modified cellulose is shown in [Figure number missing]. Figure 7 .

[0084] This embodiment further provides a nanocellulose—oxoanhydride-modified nanocellulose, the preparation method of which includes the following steps:

[0085] The oxamanic anhydride-modified cellulose was redispersed in water to prepare a cellulose suspension with a mass fraction of 0.5-0.6%, the pH was adjusted to 9.0, and then ultrasonic treatment was performed for 10 minutes to obtain oxamanic anhydride-modified nanocellulose with a diameter of 2-6 nm, a length of 400-800 nm, and an aspect ratio of 169±73.

[0086] The carboxyl content in the norbornene group-modified nanocellulose was determined by conductivity titration, and the result showed that the value was 0.66 mmol / g.

[0087] Furthermore, hydrophobic cellulose and hydrophobic nanocellulose were prepared according to Example 1. The hydrophobic angles of the two were measured to be 116° and 135°, respectively. The water contact angle images of the hydrophobic cellulose and hydrophobic nanocellulose prepared in Example 2 are shown below. Figure 8 .

[0088] Example 3

[0089] This embodiment first provides a modified cellulose—bamboo-based cellulose modified with norborneol anhydride, the preparation method of which includes the following steps:

[0090] 1) Bamboo powder was divided into 40 parts by weight. 30-60 mesh bamboo powder was selected using a sieve and soaked in water. Then, it was dried in an 85℃ oven to obtain thin-walled cells and bamboo fibers. These were then soaked in water again and dried in an 85℃ oven, repeating this process four times. Next, both were soaked sequentially in an 8% peracetic acid solution and a 5% potassium hydroxide solution, respectively, and heated simultaneously in an 85℃ oven for 5 hours. Finally, the samples were washed with water to obtain bamboo-based cellulose from the thin-walled cells and bamboo fibers, respectively.

[0091] 2) Prepare a dimethyl sulfoxide (DMSO) / potassium hydroxide (KOH) / water (H2O) standard solvent. Dissolve 4 parts of KOH in 60 parts of water, then add 440 parts of DMSO to dissolve, and shake to mix.

[0092] 3) Weigh 20 portions of the bamboo-based cellulose from step 1) above by dry weight, add it to a DMSO / KOH / H2O quasi-solvent, and pre-activate it under microwave for 10 seconds.

[0093] 4) Weigh 164 parts of norbornene, dissolve the weighed norbornene in 220 parts of DMSO, and then add it to the pre-activated bamboo fiber mixture in step 3). React at 85°C for 1 hour, then wash with water and filter until neutral to obtain norbornene-modified cellulose.

[0094] This embodiment further provides a nanocellulose—norbornyl anhydride-modified bamboo-based nanocellulose, the preparation method of which includes the following steps:

[0095] The norborneol-modified cellulose was redispersed in water to prepare a cellulose suspension with a mass fraction of 0.5-0.6%, the pH was adjusted to 9.0, and then the suspension was processed four times using a high-pressure homogenizer to obtain norborneol-modified bamboo-based nanocellulose with a diameter of 2-3 nm, a length of 600-1100 nm, and an aspect ratio of 319±110.

[0096] The carboxyl content in the norbornene group-modified nanocellulose was determined by conductivity titration, and the result showed that the value was 0.64 mmol / g.

[0097] Among them, the physical images of the norborneol-modified cellulose and the norborneol-modified bamboo-based nanocellulose are shown in [the image]. Figure 9 Characterization diagram of norbornene-modified cellulose is shown below. Figure 10 .

[0098] Furthermore, hydrophobic cellulose and hydrophobic nanocellulose were prepared according to Example 1. The hydrophobic angles of the two were tested to be 82° and 102°, respectively. The water contact angle images of the hydrophobic cellulose and hydrophobic nanocellulose prepared in Example 3 are shown below. Figure 11 .

[0099] Example 4

[0100] This embodiment first provides a modified cellulose—norborneol-modified microcrystalline cellulose, the preparation method of which includes the following steps:

[0101] 1) Prepare a dimethyl sulfoxide (DMSO) / potassium hydroxide (KOH) / water (H2O) solvent: Dissolve 4 parts KOH in 100 parts water, then add 300 parts DMSO to dissolve, and shake to mix.

[0102] 2) Weigh 20.0 parts of dry microcrystalline cellulose and add it to the DMSO / KOH / H2O quasi-solvent prepared in step 1). Pre-activate it under microwave for 10 seconds to obtain pre-activated cellulose slurry.

[0103] 3) Weigh 81 parts of norbornene, dissolve the weighed norbornene in 110 parts of DMSO, and then add it to the pre-activated cellulose slurry in step 2). React at room temperature for 10 minutes, then wash with water and filter until neutral to obtain norbornene-modified cellulose.

[0104] This embodiment further provides a nanocellulose—norbornene group-modified nanocellulose, the preparation method of which includes the following steps:

[0105] The norbornene-modified cellulose was redispersed in water to prepare a cellulose suspension with a mass fraction of 0.5–0.6%, the pH was adjusted to 9.0, and then sonicated for 10 minutes to obtain norbornene-modified nanocellulose. The carboxyl content was determined by conductivity titration, with a value of 0.80 mmol / g.

[0106] Example 5

[0107] This embodiment first provides a modified cellulose—norborneol-modified microcrystalline cellulose, the preparation method of which includes the following steps:

[0108] 1) Prepare a dimethyl sulfoxide (DMSO) / potassium hydroxide (KOH) / water (H2O) solvent: Dissolve 4 parts KOH in 60 parts water, then add 440 parts DMSO to dissolve, and shake to mix.

[0109] 2) Weigh 20.0 parts of dry microcrystalline cellulose and add it to the DMSO / KOH / H2O quasi-solvent prepared in step 1). Stir at room temperature for 10 minutes to obtain pre-activated cellulose slurry.

[0110] 3) Weigh 81 parts of norbornene, dissolve the weighed norbornene in 110 parts of DMSO, and then add it to the pre-activated cellulose slurry in step 2). React at room temperature for 10 minutes, then wash with water and filter until neutral to obtain norbornene-modified cellulose.

[0111] This embodiment further provides a nanocellulose—norbornene group-modified nanocellulose, the preparation method of which includes the following steps:

[0112] The norbornene-modified cellulose was redispersed in water to prepare a cellulose suspension with a mass fraction of 0.5-0.6%. The pH was adjusted to 9.0, and then the suspension was sonicated for 10 minutes to obtain norbornene-modified nanocellulose. The carboxyl content was determined by conductivity titration, and the value was 0.55 mmol / g.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing nanocellulose, characterized in that, include: S1: Add 10-30 parts of cellulose to a mixed solvent containing 260-550 parts of dimethyl sulfoxide, 4-8 parts of strong alkali and 20-100 parts of water, and pre-activate it under microwave for 10-60 seconds to obtain pre-activated cellulose slurry; S2: The pre-activated cellulose slurry is mixed with an esterifying agent and subjected to an esterification reaction to obtain modified cellulose; S3: The modified cellulose is mixed with water to obtain a modified cellulose suspension; the pH of the suspension is adjusted to alkaline, and then subjected to ultrasonic treatment or high-pressure homogenization to obtain nanocellulose. The esterifying agent is norbornene anhydride or oxanoic anhydride.

2. The method for preparing nanocellulose according to claim 1, characterized in that, The strong base includes one or more of potassium methoxide, potassium tert-butoxide, sodium hydroxide, and potassium hydroxide.

3. The method for preparing nanocellulose according to claim 1, characterized in that, In step S2, 40-168 parts of the esterifying agent are mixed with 10-30 parts of the pre-activated cellulose slurry, and an esterification reaction is carried out at 20-100°C. After the reaction is completed, the mixture is washed with water and filtered until neutral to obtain modified cellulose.

4. The method for preparing nanocellulose according to claim 1, characterized in that, The pH of the suspension was adjusted to 8-10.

Citation Information

Patent Citations

  • Carboxyl nano-cellulose and preparation method thereof

    CN113307888A

  • Double-bond-rich nanofiber gel prepared by chemical vapor deposition method as well as preparation method and application of double-bond-rich nanofiber gel

    CN115304789A

  • Method for producing anion-modified cellulose nanofibers

    WO2020100980A1

  • KR20200028680A